ICT ADOPTION IN EMERGING CONTEMPORARY MARKETING PRACTICES: THE CASE OF THE NIGERIAN PAINTS INDUSTRY - OLOMU, Michael Oluwaseun; IREFIN, Isaac Adeyemi; OLOMU, Olubunmi Eniola (Ecoforum Journal, 2016)
The growing awareness of firms about the deployment of information and communications technology continued to stimulate competitive advantage for them in the marketplace. This study investigated the numerous information and communications technologies deployed for products marketing in the Nigerian paints industry and also examined the degree of capacity in which ICTs were deployed in relations to contemporary marketing practices. This study considerably administered 240 questionnaire on paints manufacturing and marketing firms in Nigeria which resulted to 84.5% response rate in year 2014. The outcomes of the analysis revealed that the telephone and e-mail were widely embraced for marketing in the Nigerian paints industry. It was also discovered that paints companies adopted ICT more in a reinforcing capability as against enhancing and transforming purposes. The study suggested that paints producing and marketing firms in Nigeria need to incorporate more of ICT facilities and utilize the various offers of electronic marketing for their daily operations and automations thereby improving firm’s profitability and performance. More importantly, attention should be shifted on companies’ capability to innovate and consequently introducing new ICT products and services in the market.